Peningkatan Pemahaman Perilaku Hidup Bersih dan Sehat (PHBS) melalui Edukasi Interaktif pada Siswa SDN Bataan 2 Bondowoso - Rahma Dwi Lestari; Citra Crysantee Gracia Nusantara; Salsa Dyah Pratiwi; M. Reza Hafid Al Faris; Farah Salsabila Hakim; Putri Dwi Andita; Weldy Nugroho Detagory; Agung Nugroho Puspito (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This community service activity was motivated by the low understanding of students regarding Clean and Healthy Living Behavior (PHBS) at SDN Bataan 2 Bondowoso. The objective of the activity was to improve students' understanding of PHBS through interactive education. The methods used included lectures, game-based learning, direct practice, and discussions on four materials, namely balanced nutrition, physical activity, personal hygiene, and environmental cleanliness. Evaluation was carried out using a written pre-test and oral post-test administered to 18 students in grades IV and V. The results showed an increase in student understanding across all materials. The highest increase occurred in personal hygiene at 44%, followed by environmental cleanliness at 37%, physical activity at 19%, and balanced nutrition at 6%. Direct practice was proven to help students understand PHBS material more readily than theoretical learning alone. This activity demonstrates that interactive learning is capable of improving PHBS understanding among elementary school students.